Pengaruh implementasi Netamax-FP Unila terhadap keragaman dan kelimpahan nematoda dalam tanah pada pertanaman guava kristal di Lampung - Aulia Shalsha Saharani; I Gede Swibawa; Selvi Helina; Radix Suharjo (Jurnal Proteksi Agrikultura, 2026)
Crystal guava (Psidium guajava L.) is a horticultural plant whose fruit is widely known and as a favorable fruit in Indonesia. Crystal guava productivity in Lampung is relatively lower compared to that in Central Java and East Java. One of the factors causing a decline in crystal guava production is pest attack, including plant-parasitic nematodes. The aim of this study was to determine the effect of Netamax-FP Unila bionematicide application on the composition of the nematode community and its effects on the diversity and abundance of nematodes in crystal guava plantations at PT Great Giant Food. The research was conducted from September 2023 to March 2024. Nematode observations were carried out before and after application bionematicide. Nematodes were identified to the genera taxonomic level. Nematode diversity was measured using the number of genera, funtional groups, the Shannon-Wiener index, species richness index, species evenness index and Simpson's index. Nematode abundance was measured base on the number of individuals of each genus. The research results showed that 16nematode genera were identified. These genera were classified into three functional groups, including parasitic nematodes (herbivores), bacterial-feeding nematodes (bacterivores), and fungal-feeding nematodes (fungivores). The application of the Netamax-FP Unila bionematicide combined with compost reduced the abundance of plant-parasitic nematodes without having a negative impact on free-living nematodes or overall nematode diversity.